The Performance of Tumor Size as Risk Stratification Parameter in Upper Tract Urothelial Carcinoma (UTUC) - Foerster, Beat; Abufaraj, Mohammad; Mari, Andrea; Seisen, Thomas; Bandini, Marco; Schweitzer, Donald; Czech, Anna K; Moschini, Marco; D'Andrea, David; Bianchi, Marco; Hendricksen, Kees; Rouprêt, Morgan; et al. (Clinical genitourinary cancer, 2021)
INTRODUCTION: The objective of this study was to evaluate the performance of different tumor diameters for identifying ≥ pT2 upper tract urothelial carcinoma (UTUC) at radical nephroureterectomy. PATIENTS AND METHODS: This was a multi-institutional retrospective study that included 932 patients who underwent radical nephroureterectomy for nonmetastatic UTUC between 2000 and 2016. Tumor sizes were pathologically assessed and categorized into 4 groups: ≤ 1 cm, 1.1 to 2 cm, 2.1 to 3 cm, and > 3 cm. We performed logistic regression and decision-curve analyses. RESULTS: Overall, 45 (4.8%) patients had a tumor size ≤ 1 cm, 141 (15.1%) between 1.1 and 2 cm, 247 (26.5%) between 2.1 and 3 cm, and 499 (53.5%) > 3 cm. In preoperative predictive models that were adjusted for the effects of standard clinicopathologic features, tumor diameters > 2 cm (odds ratio, 2.38; 95% confidence interval, 1.70-3.32; P < .001) and > 3 cm (odds ratio, 1.81; 95% confidence interval, 1.38-2.38; P < .001) were independently associated with ≥ pT2 pathologic staging. The addition of the > 2-cm diameter cutoff improved the area under the curve of the model from 58.8% to 63.0%. Decision-curve analyses demonstrated a clinical net benefit of 0.09 and a net reduction of 8 per 100 patients. CONCLUSION: The 2-cm cutoff appears to be most useful in identifying patients at risk of harboring ≥ pT2 UTUC. This confirms the current European Association of Urology guideline's risk stratification. Tumor size alone is not sufficient for optimal risk stratification, rather a constellation of features is needed to select the best candidate for kidney-sparing surgery.
Keywords: prognóza; Prognosis; karcinom z přechodných buněk; Nephroureterectomy; retrospektivní studie; lidé; nefroureterektomie; hodnocení rizik; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; nádory močového měchýře; Retrospective Studies; Risk Assessment; Humans